A contingent valuation-multicriteria analysis case study on the taxonomy of three planning scenarios for a Coastal Zone of Sardinia (Italy) - Corrado Zoppi (European Regional Science Association (ERSA), 2004)
Research in the field of urban economics has defined methodologies to assess the degree of consensus of the local communities for policies that derive from land planning decisions. The contingent valuation methods, which are based on people's expressed thoughts and convic-tions, allow us on the one hand to evaluate their degree of consensus, and, on the other, to in-crease the level of public information and concern towards land planning policies. Undoubt-edly, participation, concern, information and consensus must be deeply tied to each other in order to develop open processes, based on land planning policies, that generate consistency between the planning policies goals and the spatial organization of the city that the local communities would like to realize. In this essay, a case study of contingent valuation is discussed, based on the dichotomous-choice-with-follow-up technique, to rank three planning scenarios concerning the reorganiza-tion of public services and infrastructure for outdoor recreation in the coastal zone of the town of Arbus. Through this technique, the three proposals are ranked with reference to the local community preferences and attitudes concerning a set of decision criteria. The weights of the decision criteria are defined considering the results of the contingent valuation application, and utilized in a multicriteria analysis, developed through the AHP (Analytical Hierarchy Process), in order to obtain two rankings of the proposed scenarios: the first ranking is based on the results of the contingent valuation application; the second ranking comes from the weights of the decision criteria derived from the local community preferences. These two alternative rankings give the local planning context (the city administration, entre-preneurs of the profit and non-profit sectors, citizens, civic associations and committees, etc.) a comprehensive frame of the game rules of the decision-making processes, and a sound basis for discussing, recognizing and understanding their mutual convergences and conflicts. This would allow them to define an effective synthesis of their perceived needs, hopes and expecta-tions for the future spatial organization of their city, in view of the implementation of the planning policies. This essay has a marked methodological feature since a general framework- even if perfecti-ble- which should bring near technical and common knowledge is defined in the practice of city planning. This is implemented through discussion and conflict mitigation concerning the relative importance (and weights) of the decision criteria. This should lead to a more-or-less extensive convergence on policy implementation within the city planning processes.
Keywords: 330